Cv Buana Convection Employee Training to Optimize Productivity and Skills - Supriyadi; Dimas Hadi Prayetno; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Formosa Journal of Applied Sciences, 2023)
The Buana Convection sewing business is a convection engaged in services that is growing rapidly in Karawang. This business involves the production of clothing, accessories and other textile goods through sewing processes using sewing machines. This industrial visit to CV Buana Convection uses descriptive and observative methods. training of employees in the sewing business aims to improve their skills and knowledge in sewing. Such training can cover various aspects, such as sewing techniques, fabric selection, pattern understanding, product manufacturing, inventory management and sales. It is important for sewing business owners to identify the training needs of their employees and develop a program to suit those needs. In the digital era, technology also plays an important role in the sewing business.